2015
DOI: 10.5812/numonthly.24611
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Sleep Related Disorders of Restless Leg Syndrome in Hemodialysis Patients

Abstract: Background:Despite being frequently described, Restless Leg Syndrome (RLS) in patients, who are on hemodialysis, is a common disease which, has not been well documented in Iran.Objectives:The current study aimed to investigate the prevalence of RLS and its sleep disorders in Iranian patients on hemodialysis.Patients and Methods:In this multicenter cross sectional study, 397 consecutive patients on hemodialysis were evaluated by face-to-face interviews. RLS was diagnosed using the International RLS Study Group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
28
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 27 publications
3
28
2
Order By: Relevance
“…Chavoshi et al reported the prevalence of RLS was about 31.7% in hemodialysis patients in Tehran, Iran (2). Al-Jahdali et al evaluated 227 ESRD patients in Jeddah, Saudi Arabia.…”
Section: Discussionmentioning
confidence: 99%
“…Chavoshi et al reported the prevalence of RLS was about 31.7% in hemodialysis patients in Tehran, Iran (2). Al-Jahdali et al evaluated 227 ESRD patients in Jeddah, Saudi Arabia.…”
Section: Discussionmentioning
confidence: 99%
“…[1] We also found no significant relationship between them in our study of 397 HD patients. [10] We did find a significant correlation between endocrine glandular disorders and antihypertensive drugs (p=0.03 and p=0.01, respectively) with RLS, which Demircioğlu et al did not look at in their study. [1] Several studies have demonstrated indicative association between RLS and higher risk of nocturnal hypertension, heart disease and stroke, as well as association with other sleep disturbances that could lead to anxiety and depression.…”
mentioning
confidence: 67%
“…[9] We have observed a prevalence rate of 31.7% in Iran. [10] Thus, it seems this variation in prevalence may be due to geographic and racial differences, as well as diversity in lifestyle and in criteria, and physicians' experience diagnosing RLS.…”
mentioning
confidence: 99%
“…RLS/WED is common among patients with end‐stage renal disease, with prevalence higher than in the general population (Tachibana, ). One cross‐sectional study of patients on hemodialysis revealed that the prevalence of RLS/WED was 31.7% and was dominant in females (Chavoshi, Einollahi, Sadeghniat Haghighi, Saraei, & Izadianmehr, ).…”
Section: Restless Legs Syndrome or Willis‐ekbom Diseasementioning
confidence: 99%
“…Awakened by the sensations, patients get out of bed to walk to relieve the symptoms during the night, which disrupts their sleep (Einollahi & Izadianmehr, ). In patients on hemodialysis with RLS, daytime sleepiness, insomnia, and low sleep quality were commonly reported when compared with those without RLS (Chavoshi et al, ). Moreover, RLS symptoms that start early during the day may prevent patients from keeping still during hemodialysis, affecting their participation (Tachibana, ).…”
Section: Restless Legs Syndrome or Willis‐ekbom Diseasementioning
confidence: 99%